MENGUAK PETUAH-PETUAH MORAL IBN AL-MUQAFFA SERTA RELEVANSINYA DALAM KEHIDUPAN (Telaah Terhadap Kitab al-Adab al-Shaghîr wa al-Adab al-Kabîr) (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2022)
Ibn al-Muqaffa mastered various languages ​​such as Arabic, Syriac, Pahlavi, Sanskrit, India and Greece. He studied and learned a lot of history and civilization of Persia and he also likes to read long texts with such capabilities. He was the first to translate the works of Persian and Indian literature into Arabic. Translating that resulted in two very important things: the displacement of the Arabs of  Bedouin life-style to modern living and non-Arab involvement in the writing of Arabic literature. Kitab Al-Adab al-Shagîr wa al-Adab al-Kabîr is a treatise containing moral advices. Advices were taken to Ibn al-Muqaffa from the wise words of those who passed away were very useful to cleanse our hearts and thoughts turn. Advices contained in the book are felt at all, touched the hearts of our exciting and thought-provoking.